Effects of Fuzhenghuayu decoction on collagen synthesis of cultured hepatic stellate cells, hepatocytes and fibroblasts in rats - Liu, Cheng (World J Gastroenterol, 1998)
AIM: To study the mechanism of Fuzhenghuayu (FZHY) decoction on anti-liver fibrosis. METHODS: FZHY 10% decoction sera was incubated with rat normal subcultured hepatic stellate cells (HSC) and fibrotic primarily cultured HSC, normal and fibrotic hepatocytes and subcultured skin fibroblasts seperately. Cell intracellular and extracellular collagen synthesis rates were measured by the method of [(3)H] Proline impulse and collagenase digestion. RESULTS: For primarily cultured HSC and hepatocytes, both of intracellular and extracellular collagen synthesis rates decreased in the drug sera group. For the normal subcultured HSC and primarily cultured hepatocytes, the extracellular collagen secretion was decreased obviously by the drug sera, and intracellular collagen synthesis rates were inhibited to some extents. For fibroblasts, both intracellular and extracellular collagen synthesis rates were inhibited somewhat, but no significant differences were found. CONCLUSION: The mechanism of FZHY decoction on anti-liver fibrosis may be associated with inhibition of liver collagen production.